Using DEA to evaluate efficiency of higher education - Tóth, Réka (Applied Studies in Agribusiness and Commerce, 2009)
The aim of the higher education reform process both in Hungary and in the European countries is establishing a competitive, qualitative higher education with efficiently operating institutions. The question of efficiency needs increased attention not only because of the decline of the state support but also the rapid raise of the student mass. In the educationsystemit’snot easy to measurethe output of the services.The situation is more complicated if an organisation or a sector has multiple inputs and outputs. In this case a possible method of determining efficiency is Data Envelopment Analysis. In my paper I’d like to introduce this method and use it to compare the efficiency of higher education systems. urthermore I am examining whether their efficiency is influenced by the extent of the contribution of the state and the private sector or socio-economic factors like GDP per capita and education level of parents.